Association between environmental mercury exposure and allergic disorders in Korean children: Korean National Environmental Health Survey (KoNEHS) cycles 3–4 (2015–2020) - Ji-youn Lee; Yun-Hee Choi; Hyeon-il Choi; Kyong Whan Moon (Scientific Reports, 2024)
Abstract Although previous studies have suggested potential adverse effects of mercury on a child’s immune system, the associations have been inconsistent. We aimed to determine the association between urinary mercury levels and allergic diseases in Korean children with high mercury exposure. Data from 853 and 710 children aged 6–11 years in the Korean National Environmental Health Survey (KoNEHS) cycle 3 (2015–2017) and cycle 4 (2018–2020) were analyzed. We examined the association between mercury exposure and the prevalence of atopic dermatitis (AD), asthma, allergic rhinitis (AR), and allergic multimorbidity. After adjusting for all covariates, the urinary mercury level was positively associated with AD in the 2015–2017 study (OR = 1.34, 95% CI = 1.01, 1.79) and AR in 2018–2020 study (OR = 1.46, 95% CI = 1.01, 2.10). Pooled effects showed OR of 1.34 (95% CI = 1.01, 1.79) for AD and 1.47 (95% CI = 1.01, 2.12) for allergic multimorbidity. The association with allergic multimorbidity was greater in boys (OR = 1.88, 95% CI = 1.01, 3.49) than in girls (OR = 1.25, 95% CI = 0.73, 2.14). These results suggest that environmental mercury exposure may exacerbate symptoms of atopic dermatitis and allergic multimorbidity in children.